ANALISIS FAKTOR KEPUASAN TAMU DIKYRIAD HOTEL BUMIMINANG PADANG - Hardiyanti, Dwi Yulia; Wulansari, Nidia (Jurnal Manajemen Perhotelan dan Pariwisata, 2023)
Hotel guest satisfaction is one of the most important factors in the development of the hotel. If guest satisfaction is fulfilled then the goals of the company will be achieved. Therefore, guest satisfaction is very important in a company. This study aims to analyze what factors affect guest satisfaction and analyze the most dominant factors in influencing guest satisfaction at Kyriad Hotel Bumiminang Padang.. This study used quantitative research with a descriptive approach. A total sample of 127 people was recruited using the saturated sampling method. The data collection technique uses questionnaires arranged based on Likert scales. Hypothesis testing uses a factor analysis test using SPSS version 25. The Kaiser Meyer Olkin (KMO) test value of 0.724 > 0.5 until it is stated that the right factor analysis is used to analyze the data obtained. While the results of Barlett's Test of Sphericity stated the significance results at 0.000 < 0.5 so that it can be concluded that there is a significant correlation matrix with a number of factors. Based on the total value of Variance Explained, there are 6 factors that are formed and have eigenvalues > 1 so that it can be concluded from this study that there are 6 factors formed that affect guest satisfaction at Kyriad Hotel Bumiminang Padang.